The Effect of the Traditional Hide-and-Seek Game on the Gross Motor Development of Children Aged 5–6 Years at TK Negeri Perjuangan Tanjung Angin Nupabomba Donggala Regency - Dwi Purwaningsih; Durrotunnisa Durrotunnisa; Armina Armina; Andi Agusniatih (Journal of Educational Sciences, 2026)
Child motor development plays a critical role in supporting overall developmental aspects. Physical movement limitations can significantly diminish self-confidence and foster a negative self-concept in early childhood. This study investigates the impact of the traditional hide-and-seek game on gross motor development at TK Negeri Perjuangan Tanjung Angin Nupabomba. Utilizing a quantitative approach, the research observed three specific indicators: running strength, running speed, and agility. The findings demonstrate that the traditional hide-and-seek game positively influences gross motor skills. Pre-intervention data revealed low proficiency: for running strength, 0% reached Developed Extremely Well (BSB), 25% Developed as Expected (BSH), 50% Starting to Develop (MB), and 25% Undeveloped (BB). Similar trends were observed in speed (25% BSH, 50% MB, 25% BB) and agility (12.5% BSH, 50% MB, 37.5% BB). Following the intervention, significant improvements were recorded. Running strength improved to 25% BSB and 0% BB; speed reached 12.5% BSB and 62.5% BSH; and agility increased to 12.5% BSB and 50% BSH, with 0% remaining in the BB category across all aspects. This study concludes that hide-and-seek is an effective method to enhance physical strength, speed, and agility, making it a recommended instructional strategy for early childhood physical education.